The Academic Job Market in U.S. Geography and the Business Cycle: The Long Shadow of the 2007–2009 Recession. Issue 4 (2nd October 2022) - Coomes, Oliver T.; Abizaid, Christian; Breau, Sébastien; Moore, Tim R.
Abstract : The Great Recession of 2007–2009 had profound effects on all sectors of the U.S. economy. In this article we assess the relationship between the academic job market in U.S. geography and the business cycle. Specifically, we examine the responsiveness of the job market to the business cycle since the early 1970s, the impacts of the Great Recession on hiring, and how hiring networks changed with the recession. For our analyses we draw on data from American Association of Geographers (AAG) publications, principally the AAG Newsletter (Jobs in Geography) and the Guide to Geography Programs in the Americas . We find that (1) the academic job market in geography is tightly linked to the business cycle and highly vulnerable to recessions, (2) the 2007–2009 recession destabilized demand and supply in the market with impacts on hiring lasting at least ten years, and (3) hiring networks among PhD-granting programs contracted, had lower connectivity, and witnessed a reshuffling of the top-hiring schools postrecession. Overall, the Great Recession dampened the likelihood of securing a tenure-track position in U.S. geography more so than any recession over the past fifty years. The arrival of COVID-19 and the accompanying contraction of gross domestic product are likely to further adversely affect faculty hiring. Key Words: economic recession, employment, higher education, university jobs.